A Critical Review of Available Retrievable Inferior Vena Cava Filters and Future Directions - Montgomery, Jennifer P.; Kaufman, John A. (Seminars in Interventional Radiology, 2016)
Inferior vena cava filters have been placed in patients for decades for protection against pulmonary embolism. The widespread use of filters has dramatically increased owing at least in part to the approval of retrievable vena cava filters. Retrievable filters have the potential to protect against pulmonary embolism and then be retrieved once no longer needed to avoid potential long-term complications. There are several retrievable vena cava filters available for use. This article discusses the different filter designs as well as the published data on these available filters. When selecting a filter for use, it is important to consider the potential short-term complications and the filters' window for retrieval. Understanding potential long-term complications is also critical, as these devices are approved for permanent placement and many filters are not retrieved. Finally, this article will address research into new designs that may be the future of vena cava filtration.
Keywords: inferior vena cava filter; pulmonary embolism; deep venous thrombosis; venous thromboembolic event; interventional radiology